# algebra

posted by .

use the quadratic formula to solve the equation 2x^2-3x=-6

• algebra -

2x^2 - 3x + 6 = 0.
x = 3+- sqrt(9 - 48) / 4 =
3 +- sqrt(-39) / 4 =
(3 +- sqrt(39*-1)) / 4
sqrt(-1) = i
x = +- isqrt(39) / 4
Solution Set:
x =(3 - isqrt(39)) / 4
x =(3 + isqrt(39)) / 4

## Similar Questions

1. ### Math

Use the quadratic formula to solve each of the following quadratic equations... 1. 2x^2-5x=3 2. 3x^2-2x+1=0 Rearrange the equation in quadratic formula form. 2x^2 -5x -3 = 0 Then use the formula. Tell me what you don't understand about …
2. ### algebra

use the quadratic formula to solve the equation 4x^2-7x-2=0
3. ### algebra

Use the quadratic formula to solve the equation x^2-5x=-10
4. ### algebra II

I'm quite clueless as to how to solve this. I know the quadratic equation but am not sure how to get this equation into the format to plug in to the quadratic... Solve the quadratic equation using the formula [1/(1+x)]-[1/(3-x)]=(6/35) …
5. ### algebra 1

Use the Quadratic Formula to solve the equation: 5x^2 + 9x - 2=0 -2,1/5?
6. ### algebra 1

Use the Quadratic Formula to solve the equation: 5x^2 - 6x - 8=0 -.51,1.71?
7. ### math

(4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 Rearrange to get an expression of the form ax2 + bx + c = 0 and use the quadratic formula (solve for x. This gives: x = 1.05E-2, 0.143 basically i understand they …
8. ### algebra

Use the quadratic formula to solve the equation. x^2-7x-6=0
9. ### Algebra

Use the Quadratic formula to solve the equation -4x^2-3x+2=0
10. ### Algebra

Solve the equation. Use factoring or the quadratic formula, whichever is appropriate. Try factoring first. If you have any difficulty factoring, then go right to the quadratic formula. (Enter your answers as a comma-separated list.) …

More Similar Questions